The Study of Factors that Influence Organizational Performance: Evidence from Companies in the Lower Northern Region of Thailand - Sumkaew, Nuatip; Intanon, Ruankwan (Journal of Accounting, Business and Finance Research, 2021)
A dynamic business environment focuses on corporate profit and performance. Consequently, managers need strategically relevant information to formulate and implement business strategies in order to achieve business growth and survive in an uncertain economic environment. The purpose of this study is to examine the interaction effects of environmental uncertainty and strategic management accounting (SMA) on organizational performance. The configurations are derived from a sample of 166 medium and large firms in the lower northern region of Thailand. A quantitative method is used for data collection through a survey design approach using a questionnaire. Contingency theory is employed in this study. The results indicate that a fit between environmental uncertainty and strategic management accounting has a positive, direct relationship with organizational performance. Moreover, a higher level of environmental uncertainty will improve organizational performance. As previous studies have not fully addressed the interactive linkage, this study provides evidence of how key factors can interact to promote organizational performance.